Mudanças fonológicas e metafonológicas em crianças com desvio fonológico submetidas à fonoterapia - Freitas, Giséli Pereira de (2011)
This research has the objective of checking the phonological and metaphonological changes in children with phonological deviation (PD), from the treatment with two different therapy models (Metaphon and Minimal Pairs Therapy), highlighting the phonological changes post-treatment, the different types of structural generalization achieved and the abilities in the phonological awareness (PA). . The sample was constituted by four subjects (S1, S2, S3 and S4) aged between 4:6 and 7:0. S1 and S2, females, were treated with the Metaphon Theory, while S3 and S4, males, were treated with the Minimal Pair Approach. In the pre-treatment period, phonological and extra evaluations were done to diagnose the PD. In the data collection the phonological system (PS) and the phonological awareness (PA) were evaluated and these results were also collected during the post-treatment period. During the analysis of the PS and the PA evaluation in the pre and post-treatment, it was noticed that all the subjects improved. Regarding the PS, the four subjects of the sample improved and all of them presented some kind of structural generalization: S1 and S3 overcame the PS and S2 and S4 acquired some phonemes. Regarding the PA, it was expected a bigger improvement on the subjects treated with the Metaphon compared to the ones treated with the Minimal Pair Therapy. Even though all the subjects in the study improved the abilities in the PA, it was expected, at his age, that S3 accomplished the tasks in the phonemic awareness level, but he did not succeed. It is possible to conclude that all the subjects were benefited from the treatment with both therapy models. Meaningful phonological changes were noticed after the treatment, considering that all the subjects presented different types of structural generalization. Regarding the PA, all of them improved in the tasks of syllabic awareness. In the tasks of phonological awareness just S3 (the only one who could accomplish them, according to the age) treated with the Minimal Pair Therapy, was not successful. This suggests that this model may not benefit the phonemic awareness as efficiently as the Metaphon Therapy.